The use of information and communication technologies to support working carers of older people – a qualitative secondary analysis. (15th June 2015) - Andersson, Stefan; Magnusson, Lennart; Hanson, Elizabeth
Abstract : Background: Family care support services have mainly focused on older spousal carers of older people and have largely overlooked working carers, whom combine paid work with informal/family care responsibilities. Recently, however, information and communication technology (ICT) systems have been identified as a potentially flexible way of supporting working carers. Aim: The aim of this study was to describe nursing and support staff's experiences of using ICT for information, e‐learning and support of working carers of older people. Design: The study employed a descriptive, qualitative approach conducting a qualitative secondary analysis of two original data sets. In total, seventeen professional staff members from two municipal family carer support units in Sweden that had implemented ICTs were interviewed using a semi‐structured interview guide consisting of open‐ended questions. Method: Two data sets were merged using latent qualitative content analysis. Findings: Secondary analysis produced three subthemes and an overall theme, a virtual road as a carriageway for the support of working carers, consisting of both enabling and hindering aspects in family support. This theme provides access points in both directions and is based on caring instruments that enable nursing staff's support role. The staff's sustainability and ability to support is influenced by caring opportunities and barriers. Conclusions: The findings suggest the ICTs to be flexible structures that provided nursing staff with a means and method to support working carers of older people. To overcome barriers to its use, measures to optimise support for working carers and the older person are needed. Implications for practice: The use of ICTs provides nurses with a means to offer support to working carers of older people and enables carers to be informed, to learn and to share their burdens with others when caring for an older family member.